A method for beneficiating ilmenite from a coastal sedimentary fine particle zirconium hafnium ore

CN122912988APending Publication Date: 2026-10-16GUANGXI ZHUANG AUTONOMOUS REGION GEOLOGICAL & MINERAL TESTING RES CENT +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611108269.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

采用本发明的方法获得的钛铁砂矿精矿,选矿路径为:原矿破碎-筛分分级-摇床分选-摇床精选-湿式磁选,产品二氧化钛品位54.62%,已达到质量标准YS/T 351-2015《钛铁砂矿精矿》中一级品质量要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912988A_ABST
    Figure CN122912988A_ABST
Patent Text Reader

Abstract

This invention discloses a method for beneficiating fine-grained zirconium-hafnium ore from coastal sedimentary deposits, belonging to the field of mineral processing technology. The method includes: crushing the raw ore, preparing it into a solution, stirring and dispersing it, and sieving and classifying it to obtain the following particle size products: +0.71mm, -0.71+0.3mm, -0.3+0.1mm, and -0.1mm; the -0.3+0.1mm particle size product is separated by a shaking table to obtain coarse concentrate 1 and coarse tailings 1, and the coarse concentrate 1 is further refined by a shaking table to obtain concentrate 1 and middlings 4; the -0.1mm particle size product is separated by a shaking table to obtain coarse concentrate 2 and coarse tailings 2, and the coarse concentrate 2 is further refined by a shaking table to obtain concentrate 2 and middlings 2; the magnetically separated concentrate obtained by wet magnetic separation of concentrate 1 and / or concentrate 2 is the ilmenite sand concentrate. The beneficiation path of the ilmenite concentrate in this application is as follows: raw ore crushing - screening and grading - shaking table separation - shaking table cleaning - wet magnetic separation. The titanium dioxide grade is 54.62%, which meets the first-grade quality requirements in YS / T 351-2015 "ilmenite concentrate"; the obtained quartz sand concentrate has a SiO2 grade of 98.23%, which meets the first-grade requirements in JC / T 529-2000 "silica raw materials for flat glass".
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of mineral processing technology, specifically relating to a method for beneficiating ilmenite from coastal sedimentary fine-grained zircon-hafnium ore. Background Technology

[0002] Coastal placer deposits possess advantages such as ease of mining, low cost, and high comprehensive utilization value. Their main mineral types include zircon, ilmenite, leucoxene, rutile, and anatase. Since coastal sands also contain minerals with high economic value, such as ilmenite and quartz sand, there is an urgent need to develop a comprehensive beneficiation method for coastal sands to improve resource utilization. Summary of the Invention

[0003] This invention provides a method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore to solve the above-mentioned technical problems.

[0004] To solve the above technical problems, the present invention adopts the following technical solution: A method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore includes the following steps: The raw ore was crushed, prepared into a solution, stirred and dispersed, and then sieved and classified to obtain the following particle size products: +0.71mm, -0.71+0.3mm, -0.3+0.1mm and -0.1mm; The product with a particle size of -0.3 to +0.1 mm is separated by a shaking table to obtain coarse concentrate 1 and coarse tailings 1. The coarse concentrate 1 is then further separated by a shaking table to obtain concentrate 1 and middlings 4. -0.1mm particle size product is separated by shaking table to obtain rough concentrate 2 and rough tailings 2. Rough concentrate 2 is then further separated by shaking table to obtain concentrate 2 and middlings 2. Concentrate 1 and / or concentrate 2 are subjected to wet magnetic separation to obtain zircon rough concentrate and ilmenite sand concentrate, respectively, which are screened by the magnetic properties of the minerals.

[0005] Zircon rough concentrate is further subjected to shaking table gravity separation to obtain zircon concentrate and zircon middlings. Zircon concentrate is one of the products, while zircon middlings are processed by self-return shaking table gravity separation.

[0006] Furthermore, the parameters for shaking table sorting, shaking table fine selection, and shaking table sweeping of particles in the -0.3 to +0.1 mm size range are as follows: shaking table stroke range is 9-17 mm, stroke rate range is 280-460 times / min, and table surface slope range is 0-10°.

[0007] Furthermore, the feed concentration for shaking table separation, shaking table cleaning, and shaking table scavenging of particles in the -0.3 to +0.1 mm size range is 10-20%, and the flushing water flow rate is 0.05-0.14 L / s.

[0008] Furthermore, the parameters for shaking table sorting, shaking table fine selection, and shaking table sweeping of -0.1mm particles are as follows: shaking table stroke range is 2-10mm, stroke rate range is 475-930 times / min, and table surface slope range is 1-2°.

[0009] Furthermore, the feed concentration for shaking table separation, shaking table cleaning, and shaking table scavenging of -0.1mm particle size is 15-25%, and the flushing water flow rate is 0.05-0.12L / s.

[0010] Further, the coarse tailings 1 is scavenged by a shaking table to obtain middlings 1 and middlings 5, and middlings 1 is further separated by shaking table; the coarse tailings 2 is scavenged by a shaking table to obtain middlings 3 and discharged tailings; middlings 2 and / or middlings 3 are further separated by shaking table.

[0011] Furthermore, the wet magnetic separation process uses a separation box with a 1.5mm gap, a magnetic field strength range of +7000-20000 Oe, and a pulp concentration range of 15-30%.

[0012] Furthermore, the particle size treated by wet magnetic separation is -1 mm.

[0013] Furthermore, zircon concentrate is obtained by shaking table gravity separation of zircon rough concentrate. The parameters of shaking table gravity separation are as follows: shaking table stroke range is 9-17mm, stroke rate range is 280-460 times / min, bed slope range is 0-10°, feed concentration is 15-20%, and flushing water flow rate is 0.08-0.14L / s.

[0014] Furthermore, the beneficiation of quartz sand concentrate includes: the +0.71mm particle size product is crushed, screened and classified to obtain the following particle size products: +0.71mm, -0.71+0.1mm, -0.1mm; the -0.71+0.1mm particle size product and the -0.71+0.3mm particle size product are combined with the aforementioned middlings 4 and middlings 5, and then subjected to magnetic separation to remove magnetic minerals to obtain quartz sand concentrate; the magnetic field strength of the magnetic separation is 0.7-1.6T; the -0.1mm particle size product is treated as tailings for external discharge.

[0015] Furthermore, the magnetic field strength is 1.3T.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The ilmenite concentrate obtained by the method of this invention has the following beneficiation path: raw ore crushing - screening and grading - shaking table separation - shaking table cleaning - wet magnetic separation. The titanium dioxide grade of the product is 54.62%, which meets the first-grade quality requirements of the quality standard YS / T 351-2015 "ilmenite concentrate".

[0017] The method of this invention can also be used to obtain quartz sand concentrate. The beneficiation path is: raw ore crushing - screening and grading - magnetic separation. The product quartz sand concentrate has a SiO2 grade of 98.23%, an Al2O3 grade of 0.21%, and an Fe2O3 grade of 0.058%, which meets the requirements of JC / T 529-2000 "Silica Raw Materials for Flat Glass". Requirements for Class 1 products.

[0018] The method of this invention is used to obtain zircon concentrate. The beneficiation path is as follows: raw ore crushing - screening and grading - shaking table separation - shaking table cleaning - wet magnetic separation - shaking table gravity separation. The product has a zircon dioxide grade of 50.66%, which meets the quality requirements of Grade 5 in the quality standard YS / T 858-2013 "Zircon Concentrate". Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 This is a flow chart of the mineral processing technology of the present invention. Detailed Implementation

[0021] To facilitate a better understanding of the present invention, the following examples are provided in conjunction with the accompanying drawings. These examples fall within the scope of protection of the present invention, but do not limit the scope of protection of the present invention.

[0022] Example A method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore includes the following steps: The raw ore was crushed, prepared into a solution, stirred and dispersed, and then sieved and classified to obtain the following particle size products: +0.71mm, -0.71+0.3mm, -0.3+0.1mm and -0.1mm; The product with a particle size of -0.3 to +0.1 mm is separated by a shaking table to obtain coarse concentrate 1 and coarse tailings 1. The coarse concentrate 1 is then further separated by a shaking table to obtain concentrate 1 and middlings 4. -0.1mm particle size product is separated by shaking table to obtain rough concentrate 2 and rough tailings 2. Rough concentrate 2 is then further separated by shaking table to obtain concentrate 2 and middlings 2. Concentrate 1 and / or concentrate 2 are subjected to wet magnetic separation to obtain zircon rough concentrate and ilmenite sand concentrate, respectively.

[0023] Zircon concentrate is separated by shaking table gravity separation to obtain zircon concentrate and zircon middlings. Zircon concentrate is one of the products, while zircon middlings are processed by self-return shaking table gravity separation.

[0024] The parameters for shaking table separation, shaking table fine selection, and shaking table sweeping of particles in the -0.3 to +0.1 mm size range are as follows: shaking table stroke range is 9-17 mm, stroke rate range is 280-460 times / min, and table surface slope range is 0-10°.

[0025] For shaking table separation, shaking table cleaning, and shaking table scavenging of particles ranging from -0.3 to +0.1 mm, the feed concentration is 10-20%, and the flushing water flow rate is 0.05-0.14 L / s.

[0026] The parameters for shaking table separation, shaking table fine selection, and shaking table sweeping of particles in the -0.1mm size range are as follows: shaking table stroke range is 2-10mm, stroke rate range is 475-930 times / min, and table surface slope range is 1-2°.

[0027] For shaking table separation, shaking table cleaning, and shaking table scavenging of particles in the -0.1mm size, the feed concentration is 15-25%, and the flushing water flow rate is 0.05-0.12L / s.

[0028] Coarse tailings 1 are scavenged on a shaking table to obtain middlings 1 and middlings 5. Middlings 1 is then separated on a shaking table. Coarse tailings 2 are scavenged on a shaking table to obtain middlings 3 and discharged tailings. Middlings 2 and / or middlings 3 are then separated on a shaking table. Middlings 1 can be returned to the shaking table for further separation, and middlings 3 can also be returned to the shaking table for further separation together with the preceding middlings 2.

[0029] The wet magnetic separation process uses a 1.5mm gap separation box with a magnetic field strength range of +7000-16000 Oe and a pulp concentration range of 15-30%. The particle size of the wet magnetic separation process is -1mm. After the magnetic field strength selection test of the wet magnetic separation, the best effect was achieved with a strength of 10000 Oe, which is the most suitable magnetic field strength.

[0030] Zircon concentrate is obtained by gravity separation of zircon rough concentrate and shaking table. The parameters of shaking table gravity separation are as follows: shaking table stroke range is 9-17mm, stroke rate range is 280-460 times / min, table slope range is 0-10°, feed concentration is 15-20%, and flushing water flow rate is 0.08-0.14L / s.

[0031] The beneficiation methods for quartz sand concentrate include: The +0.71mm particle size product was crushed and screened to obtain the following particle size products: +0.71mm, -0.71mm, and -0.1mm. The -0.71+0.1mm and -0.71+0.3mm particle size products are combined with the aforementioned middle ore 4 and middle ore 5, and after magnetic separation, magnetic minerals are removed to obtain quartz sand concentrate. The magnetic field strength for magnetic separation is 0.7-1.6T; after testing the magnetic field strength for magnetic separation, a strength of 1.3T was found to be the most effective and suitable.

[0032] -0.1mm particle size products are treated as tailings for external discharge.

[0033] Example 1 A method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore includes the following steps: The raw ore was crushed, prepared into a solution, stirred and dispersed, and then sieved and classified to obtain the following particle size products: +0.71mm, -0.71+0.3mm, -0.3+0.1mm and -0.1mm; The product with a particle size of -0.3 to +0.1 mm is separated by a shaking table to obtain coarse concentrate 1 and coarse tailings 1. The coarse concentrate 1 is then further separated by a shaking table to obtain concentrate 1 and middlings 4. -0.1mm particle size product is separated by shaking table to obtain rough concentrate 2 and rough tailings 2. Rough concentrate 2 is then further separated by shaking table to obtain concentrate 2 and middlings 2. Concentrate 1 and / or concentrate 2 are subjected to wet magnetic separation to obtain zircon rough concentrate and ilmenite sand concentrate, respectively.

[0034] The parameters for shaking table separation, shaking table fine selection, and shaking table sweeping of products with particle sizes of -0.3 to +0.1 mm are as follows: shaking table stroke range is 9 mm, stroke range is 280 times / min, and bed surface slope range is 1°.

[0035] The feed concentration for shaking table separation, shaking table cleaning, and shaking table scavenging of products with particle sizes of -0.3 to +0.1 mm is 10%, and the flushing water flow rate is 0.05 L / s.

[0036] The parameters for shaking table separation, shaking table fine selection, and shaking table sweeping of -0.1mm particle size products are as follows: shaking table stroke range is 2mm, stroke rate range is 475 times / min, and bed surface slope range is 1°.

[0037] The feed concentration for shaking table separation, shaking table cleaning, and shaking table scavenging of -0.1mm particle size products is 15%, and the flushing water flow rate is 0.05L / s.

[0038] The wet magnetic separation process uses a 1.5mm gap separator, a magnetic field strength range of 7000 Oe, and a pulp concentration range of 15%; the particle size of the wet magnetic separation process is -1mm.

[0039] Zircon concentrate was obtained by gravity separation of zircon rough concentrate and shaking table. The parameters of shaking table gravity separation are as follows: shaking table stroke range is 9 mm, stroke rate range is 280 times / min, table slope range is 1°, feed concentration is 15%, and flushing water flow rate is 0.08 L / s.

[0040] The beneficiation methods for quartz sand concentrate include: The +0.71mm particle size product is crushed and screened to obtain the following particle size products: +0.71mm, -0.71mm, and -0.1mm; among which, the -0.1mm particle size product is treated as tailings for external discharge.

[0041] The -0.71+0.1mm and -0.71+0.3mm particle size products were combined with the aforementioned middle ore 4 and middle ore 5, and subjected to magnetic separation using a magnetic field strength of 0.7T to remove magnetic minerals, yielding quartz sand concentrate.

[0042] Example 2 A method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore includes the following steps: The raw ore was crushed, prepared into a solution, stirred and dispersed, and then sieved and classified to obtain the following particle size products: +0.71mm, -0.71+0.3mm, -0.3+0.1mm and -0.1mm; The product with a particle size of -0.3 to +0.1 mm is separated by a shaking table to obtain coarse concentrate 1 and coarse tailings 1. The coarse concentrate 1 is then further separated by a shaking table to obtain concentrate 1 and middlings 4. -0.1mm particle size product is separated by shaking table to obtain rough concentrate 2 and rough tailings 2. Rough concentrate 2 is then further separated by shaking table to obtain concentrate 2 and middlings 2. Concentrate 1 and / or concentrate 2 are subjected to wet magnetic separation to obtain zircon rough concentrate and ilmenite sand concentrate, respectively.

[0043] The parameters for shaking table separation, shaking table fine selection, and shaking table sweeping of products with particle sizes of -0.3 to +0.1 mm are as follows: shaking table stroke range is 15 mm, stroke rate range is 380 times / min, and bed surface slope range is 3°.

[0044] The feed concentration for shaking table separation, shaking table cleaning, and shaking table scavenging of products with particle sizes of -0.3 to +0.1 mm is 15%, and the flushing water flow rate is 0.11 L / s.

[0045] The parameters for shaking table separation, shaking table fine selection, and shaking table sweeping of -0.1mm particle size products are as follows: shaking table stroke range is 6mm, stroke rate range is 725 times / min, and bed surface slope range is 2°.

[0046] The feed concentration for shaking table separation, shaking table cleaning, and shaking table scavenging of -0.1mm particle size products is 24%, and the flushing water flow rate is 0.09L / s.

[0047] Wet magnetic separation uses a separation box with a 1.5mm gap, a magnetic field strength range of 10000 Oe, a pulp concentration range of 25%, and the mineral particle size processed by wet magnetic separation is ≤1mm; The parameters for the shaking table gravity separation are as follows: the shaking table stroke range is 13mm, the stroke rate range is 372 times / min, the table surface slope range is 3°, the feed concentration is 18%, and the flushing water flow rate is 0.12L / s.

[0048] The beneficiation methods for quartz sand concentrate include: The +0.71mm particle size product is crushed and screened to obtain the following particle size products: +0.71mm, -0.71mm, and -0.1mm; among which, the -0.1mm particle size product is treated as tailings for external discharge.

[0049] The -0.71+0.1mm and -0.71+0.3mm particle size products were combined with the aforementioned middle ore 4 and middle ore 5, and subjected to magnetic separation using a magnetic field strength of 1.3T to remove magnetic minerals, yielding quartz sand concentrate.

[0050] Example 3 A method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore includes the following steps: The raw ore was crushed, prepared into a solution, stirred and dispersed, and then sieved and classified to obtain the following particle size products: +0.71mm, -0.71+0.3mm, -0.3+0.1mm and -0.1mm; The product with a particle size of -0.3 to +0.1 mm is separated by a shaking table to obtain coarse concentrate 1 and coarse tailings 1. The coarse concentrate 1 is then further separated by a shaking table to obtain concentrate 1 and middlings 4. -0.1mm particle size product is separated by shaking table to obtain rough concentrate 2 and rough tailings 2. Rough concentrate 2 is then further separated by shaking table to obtain concentrate 2 and middlings 2. Concentrate 1 and / or concentrate 2 are subjected to wet magnetic separation to obtain zircon rough concentrate and ilmenite sand concentrate, respectively.

[0051] The parameters for shaking table separation, shaking table fine selection, and shaking table sweeping of products with particle sizes of -0.3 to +0.1 mm are as follows: shaking table stroke range is 17 mm, stroke rate range is 460 times / min, and bed surface slope range is 7°.

[0052] The feed concentration for shaking table separation, shaking table cleaning, and shaking table scavenging of products with particle sizes of -0.3 to +0.1 mm is 20%, and the flushing water flow rate is 0.14 L / s.

[0053] The parameters for shaking table separation, shaking table fine selection, and shaking table sweeping of -0.1mm particle size products are as follows: shaking table stroke range is 10mm, stroke rate range is 930 times / min, and bed surface slope range is 2°.

[0054] The feed concentration for shaking table separation, shaking table cleaning, and shaking table scavenging of -0.1mm particle size products is 25%, and the flushing water flow rate is 0.12L / s.

[0055] Wet magnetic separation uses a 1.5mm gap separation box, a magnetic field strength range of 16000 Oe, a pulp concentration range of 30%, and the mineral particle size processed by wet magnetic separation is ≤1mm; Zircon concentrate was obtained by shaking table gravity separation of zircon rough concentrate. The parameters of shaking table gravity separation are as follows: shaking table stroke range is 17 mm, stroke rate range is 460 times / min, table slope range is 7°, feed concentration is 20%, and flushing water flow rate is 0.14 L / s.

[0056] The beneficiation methods for quartz sand concentrate include: The +0.71mm particle size product is crushed and screened to obtain the following particle size products: +0.71mm, -0.71mm, and -0.1mm; among which, the -0.1mm particle size product is treated as tailings for external discharge.

[0057] The -0.71+0.1mm and -0.71+0.3mm particle size products were combined with the aforementioned middle ore 4 and middle ore 5, and subjected to magnetic separation using a magnetic field strength of 1.6T to remove magnetic minerals, yielding quartz sand concentrate.

[0058] Experiment 1 I. Sampling Instructions The sampling point is located in the coastal fine-grained zirconium-hafnium sedimentary sand deposit section in Hepu County, Beihai City.

[0059] The sampling points are mainly distributed in the secondary marine terraces, with lithology mainly consisting of medium to coarse clay sand. The samples come from all the basic analysis samples, heavy sand samples, grain size distribution samples, and the remaining core samples, totaling 41 boreholes. The boreholes are evenly distributed throughout the entire survey area, and the cores are covered from the surface to the depth, are representative, and meet the requirements for mineral processing samples.

[0060] 2. Sampling Method The sampling method used was 1 / 2 or 1 / 4 core splitting, with a core diameter of 110 mm.

[0061] 3. Sample Preparation Instructions The samples were packed in about 30 white woven bags. Since the test was conducted using all the drilled sub-samples, there was no need to mix the samples at this time. All the samples were simply mixed evenly into one sample.

[0062] II. Ore Structure Study 1. Ore structure The test ore exhibits sandy, gravelly, coarse-to-medium sandy, and silty textures. It consists of rock fragments and individual minerals composed of minerals such as quartz, feldspar, sericite, kaolinite, ilmenite, and rutile, which were deposited after being transported by hydrodynamic forces. Most of the ore has a relatively good roundness, but the particle size varies considerably. Particles larger than 2 mm are classified as gravel, those between 2 and 0.06 mm as sand, those between 0.06 and 0.004 mm as silt, and those smaller than 0.004 mm as clay (i.e., mud).

[0063] 2. Ore sample structure The loosely deposited structure of ore refers to the structure formed by the loose and uneven accumulation of various minerals, such as sand, gravel, silt, and clay, together.

[0064] 3. Mineral grain size In the raw ore samples, they are more concentrated in the -0.3mm particle size samples. In the zircon concentrate of the beneficiation process test, the major diameter of zircon is mostly between 0.01-0.22mm, with some slightly larger ones, the largest reaching 0.3mm. The minor diameter is mainly between 0.005-0.1mm, with some reaching 0.12mm. Among them, the particle size of colorless transparent zircon and pink zircon is generally larger than that of rose zircon.

[0065] 4. Main mineral characteristics Zircon is one of the main useful minerals in the sample. Single-mineral qualitative and quantitative analysis of zircon using electron probe microanalysis showed that it is mainly composed of ZrO2, TiO2 and SiO2, with small amounts of Hf, Al, K, Mg and other elements.

[0066] The zircon in the ore sample is mostly in the form of subhedral columnar, broken columnar, sub-cylindrical granular, and granular, with a small amount in columnar granular and rounded granular. The roundness is low and the transport traces are not very obvious, suggesting that it is close to the parent rock. The degree of liberation of the individual minerals is above 98%, which is relatively high. The mineral structure is relatively stable and there are no other minerals embedded in it, making it relatively easy to enrich in subsequent beneficiation tests.

[0067] 5. Multiple chemical analyses of the raw ore The results of multi-element analysis of the raw ore are shown in Table 1.

[0068] Table 1. Results of multi-element analysis of raw ore

[0069] The analysis results show that zircon and ilmenite in the raw ore can be recovered; the SiO2 in the raw ore has a high grade and exists in the form of quartz sand, which is conducive to the comprehensive recovery and utilization of quartz sand in the raw ore.

[0070] 6. Raw ore screening analysis The sieve analysis results of the raw ore show that the +0.3mm size fraction has low zirconium grade and distribution, while the SiO2 grade and distribution are high. The +0.71mm size fraction contains trace amounts of zirconium-titanium minerals, mostly as inclusions. The -0.71mm and +0.3mm fractions also contain trace amounts of ilmenite. However, zircon in this size fraction primarily exists as inclusions within the quartz particles. Considering all factors, zirconium beneficiation is not performed for recovery; instead, magnetic separation is used to remove iron, and the product is intended for use in flat glass production.

[0071] Table 2 Results of screening analysis of raw ore

[0072] The valuable component ZrO2 has a distribution rate of 89.74% in the -0.3 mm particle size, and the highest grade is found in the -0.074 +0.010 mm particle size, where ZrO2 reaches over 1000 ppm. This indicates that zircon is mainly distributed in the finer particle size. The distribution rate of zircon in the -0.01 mm particle size is 36.78%. The zircon-titanium minerals are micro-fine-grained minerals, and the beneficiation and recovery of this part of zircon may be quite difficult.

[0073] The standards and instruments used for the detection and analysis of elements such as ZrO2 and TiO2 in the above-mentioned chemical analysis and sieving analysis of raw ore are consistent with those used later. The detection methods used in this application that are not described in detail are all existing technologies and will not be described in detail hereafter.

[0074] III. Mineral Processing Methods 1. Mineral processing methods Using the method of Embodiment 2 of the present invention, the collected mineral samples are subjected to crushing, screening, shaking table separation, fine selection, scavenging, and magnetic separation to obtain zircon concentrate, ilmenite concentrate, and quartz sand concentrate, respectively.

[0075] 2. Mineral processing equipment The relevant parameters of the shaking table equipment used are shown in Table 3.

[0076] Table 3. Specifications of Shaking Table Models

[0077] The parameters of the magnetic separation equipment used in mineral processing are shown in Table 4.

[0078] Table 4 Parameter Description of Magnetic Separation Equipment

[0079] 1) Magnetic separation magnetic field strength test Wet magnetic separators were used to separate magnetic iron minerals from the zirconium-titanium mixed rough concentrate obtained by gravity separation. Condition tests were conducted using different magnetic field strengths to screen for the optimal magnetic field strength.

[0080] The test results are shown in Table 5.

[0081] Table 5 Results of magnetic separation test

[0082] Analysis of the magnetic separation test results in Table 5 shows that the recovery rate of titanium varies relatively little, while the recovery rate of zirconium decreases with increasing magnetic field strength. Considering all factors, a magnetic field strength of 10000 Oe is recommended to ensure both the grade of titanium concentrate and the recovery rate of zirconium rough concentrate.

[0083] 2) Selective test of magnetic field strength for quartz sand Iron removal experiments were conducted on the quartz sand products of -0.71+0.1mm particle size, -0.71+0.3mm particle size, and the mixture of medium ore 4 and medium ore 5 using a high gradient magnetic separator. The magnetic separation equipment was a SLon-100 periodic pulse high gradient magnetic separator.

[0084] The results of the magnetic separation iron removal test are shown in Table 6.

[0085] Table 6 Results of magnetic separation for iron removal

[0086] As shown in Table 6, when the magnetic field strength reaches 1.3T, the Fe2O3 content of the quartz sand concentrate is 0.096%. Further increasing the magnetic field strength does not significantly reduce the iron content; therefore, the magnetic field strength is determined to be 1.3T.

[0087] 3. Product testing 1) Product source: Zircon concentrate, ilmenite concentrate, and quartz sand concentrate obtained by mineral processing using the method of Example 2 of this invention.

[0088] 2) Testing items The main components tested are ZrO2, HfO2, TiO2, SiO2, Fe2O3, and Al2O3.

[0089] 3) Main standards used ①The main testing standards are: GB / T 14506.3-2010 "Chemical Analysis Methods for Silicate Rocks - Part 3: Determination of Silica Content", is used to detect the content of SiO2; GB / T 14506.4-2010 "Chemical Analysis Methods for Silicate Rocks - Part 4: Determination of Aluminum Oxide Content", is used to detect the content of Al2O3; GB / T 14506.5-2010 "Chemical Analysis Methods for Silicate Rocks - Part 5: Determination of Total Iron Content", is used to detect the content of Fe2O3; GB / T 14506.6-2010 "Chemical Analysis Methods for Silicate Rocks - Part 6: Determination of Calcium Oxide Content", is used to detect the content of CaO. GB / T 14506.7-2010 "Chemical Analysis Methods for Silicate Rocks - Part 7: Determination of Magnesium Oxide Content", is used to detect the content of MgO; GB / T 14506.8-2010 "Chemical Analysis Methods for Silicate Rocks - Part 8: Determination of Titanium Dioxide Content", is used to detect the content of TiO2; GB / T 14506.29-2010 "Chemical Analysis Methods for Silicate Rocks - Part 29: Determination of 22 Elements Including Rare Earth Elements", is used to detect the content of HfO2; GB / T 17416.1-2010 "Chemical Analysis Methods for Zirconium Ore - Part 1: Determination of Zirconium-Hafnium Concentration", is used to detect the content of ZrO2; ②The main product evaluation criteria are: YS / T 858-2013 "Zirconium Concentrate"; YS / T 351-2015 "Ilmenite Sand Concentrate"; JC / T 529-2000 Silica Raw Materials for Flat Glass The standards mentioned above for product testing and evaluation are all existing technologies and will not be elaborated upon here.

[0090] 4) Main testing equipment Thermo Fisher Scientific China's inductively coupled plasma atomic emission spectrometer, model ICAP PRO X, is used to detect the content of ZrO2 and TiO2. Thermo Fisher Scientific China's inductively coupled plasma mass spectrometer, model iCAPQ, is used to detect the content of HfO2. The Rigaku X-ray fluorescence spectrometer, model ZSX Primus IV, is used to detect the content of SiO2, Fe2O3, and Al2O3.

[0091] 5) Test results The TiO2 grade of the raw ore is 0.65%, and the ZrO2 grade is 361 ppm (0.0361%). The TiO2 grade of the selected ilmenite concentrate was 54.62%, and the zircon concentrate had a zircon oxide grade of 506,631 ppm (50.66%).

[0092] The technical specifications of zircon concentrate are shown in Table 7.

[0093] Table 7. Results of multiple chemical analyses of zircon concentrate

[0094] The analysis results in Table 7 show that the ZrO2 grade is 50.66%, which meets the grade 5 quality requirements in YS / T 858-2013 "Zirconium Concentrate".

[0095] The technical indicators of the ilmenite concentrate obtained by the beneficiation method of this invention are shown in Table 8.

[0096] Table 8. Results of multiple chemical analyses of ilmenite sandstone concentrate

[0097] The analysis results in Table 8 show that the titanium dioxide grade of the ilmenite concentrate reaches 54.62%, which meets the first-grade quality requirements of the quality standard YS / T 351-2015 "ilmenite concentrate".

[0098] The technical specifications of the quartz sand concentrate are shown in Table 9.

[0099] Table 9. Results of multiple chemical analyses of quartz sand concentrate products

[0100] The analysis results of the quartz sand concentrate product in Table 9 show that the SiO2 grade is 98.23%, the Al2O3 grade is 0.21%, and the Fe2O3 grade is 0.058%. This quartz sand concentrate product meets the requirements of JC / T 529-2000 "Silica Raw Materials for Flat Glass". Requirements for Class 1 products.

[0101] The test results show that the TiO2 grade of the raw ore is 0.65%. After using the beneficiation method of the present invention, the grade is increased to 54.62%, and a higher grade of quartz sand concentrate is obtained, which makes full use of mineral resources and avoids waste of resources.

[0102] Experiment 2 1. Comparison of mineral processing 1) Use of standards and equipment The testing should be conducted in accordance with the standards and testing equipment described in section 3, "Product Testing".

[0103] 2) Sample source The sample was raw ore, taken from the ore sample collected in Experiment 1 above. After crushing and screening, two portions of the product with particle size of -0.3 and +0.1 mm and particle size of -0.1 mm were taken, each with 10 kg.

[0104] 3) Using the method of the present invention One sample of each particle size was processed using the method of Example 2 of this invention, as follows: The product with a particle size of -0.3 to +0.1 mm was separated by shaking table to enrich the coarse concentrate 2-1.

[0105] The -0.3 to +0.1 mm product obtained by sieve analysis was adjusted to a feed concentration of 15% by adding water and fed evenly to the inlet of the shaking table. The flow rate of the shaking table flushing water was 0.11 L / s. The product was filtered with filter paper, dried at 100℃, weighed, and then the contents of titanium, silicon, and zirconium were tested.

[0106] The results of testing on rough concentrate 2-1 are as follows: The TiO2 grade is 10.42%; The SiO2 grade is 77.94%; The ZrO2 grade is 5098 ppm.

[0107] The -0.1mm particle size product was separated by shaking table to enrich the coarse concentrate 2-2.

[0108] The -0.1mm product obtained by sieving was adjusted to a feed concentration of 24% by adding water and fed evenly to the inlet of the shaking table. The flow rate of the shaking table flushing water was 0.09L / s. The product was filtered with filter paper, dried at 100℃, weighed, and then the contents of titanium, silicon, and zirconium were tested.

[0109] The results of testing the rough concentrate 2-2 are as follows: The TiO2 grade is 4.07%; The SiO2 grade is 87.48%; The ZrO2 grade is 6612 ppm.

[0110] 4) Flotation comparison The remaining -0.3 to +0.1 mm particle size products were separated by flotation, enriching the rough concentrate by 2-3%. The -0.3 to +0.1 mm product obtained by sieving was adjusted to a feed concentration of 55% with water, and then ground to the -0.1 mm particle size. The slurry was poured into a 1.5 L flotation cell for flotation, with flotation reagents added sequentially (roughing: sodium silicate 500 g / t, sodium petroleum sulfonate 300 g / t; scavenging: sodium petroleum sulfonate 150 g / t), and aeration was carried out at 0.1 m³. 3 / h, scrape off the foam; filter the foam with filter paper, dry it at 100℃, weigh it again, and then test the content of titanium, silicon, and zirconium.

[0111] The results of testing on rough concentrate 2-3 are as follows: The TiO2 grade is 1.13%; The SiO2 grade is 74.25%; The ZrO2 grade is 356 ppm.

[0112] The -0.1mm particle size product in the remaining sample was separated by flotation, and the rough concentrate was enriched by 2-4.

[0113] The -0.1mm product obtained by sieving was diluted with water to adjust the feed concentration to 30% and poured into a 1.5L flotation cell. Flotation reagents were added sequentially (roughing: sodium silicate 500g / t, sodium petroleum sulfonate 300g / t; scavenging: sodium petroleum sulfonate 150g / t), and aeration was carried out to 0.1m. 3 / h, scrape off the foam; filter the foam with filter paper, dry it at 100℃, and weigh it again; then test the content of titanium, silicon, and zirconium.

[0114] The results of testing on rough concentrate 2-4 are as follows: The TiO2 grade is 1.05%; The SiO2 grade is 64.42%.

[0115] The ZrO2 grade is 616 ppm.

[0116] 5) Results Analysis -0.3 to +0.1 mm particle size mineral sample: The TiO2 grade processed by the method of this invention is 10.42%, and the ZrO2 grade is 5098 ppm; the TiO2 grade separated by flotation is 1.13%, and the ZrO2 grade is 356 ppm; Compared with the existing flotation separation process, the TiO2 grade of the method of this invention is 9.2 times that of the latter, and the ZrO2 grade is 14.3 times that of the latter.

[0117] -0.1mm particle size mineral sample: The TiO2 grade processed by the method of this invention is 4.07%, and the ZrO2 grade is 6612ppm; the TiO2 grade separated by flotation is 1.05%, and the ZrO2 grade is 616ppm; compared with the existing flotation separation process, the TiO2 grade of the method of this invention is 3.9 times that of the latter, and the ZrO2 grade of the method of this invention is 10.7 times that of the latter.

[0118] The comparison of the two sets of data above shows that, compared with flotation separation, the method of the present invention significantly improves the TiO2 grade and the SiO2 grade.

[0119] 2. Carefully selected comparisons 1) Use of standards and equipment The testing should be conducted in accordance with the standards and testing equipment described in section 3, "Product Testing".

[0120] 2) Sample source The samples were taken from concentrate 1 and concentrate 2 obtained by the method of Example 2 of the present invention, 3 kg of each, and divided into two equal parts of 1.5 kg each; wherein, the ZrO2 grade of concentrate 1 was 23913 ppm and the ZrO2 grade of concentrate 2 was 87302 ppm.

[0121] 3) Using the method of the present invention One sample was processed using the method of Example 2 of this invention, as follows: 2-1. Wet magnetic separation was used to purify ilmenite concentrate.

[0122] The rough concentrate 1 obtained from the shaking table roughing process (-0.3 + 0.1 mm) and the rough concentrate 2 obtained from the shaking table roughing process (-0.1 mm) were combined, water was added to adjust the feed concentration to 25%, and the mixture was poured into the feed funnel and stirred before being fed into the beneficiation process. The magnetic field strength was set to 10000 Oe. The mixture was filtered with filter paper, dried at 100℃, weighed, and the contents of titanium and silicon were determined.

[0123] The results of testing on ilmenite concentrate 2-1 are as follows: The TiO2 grade is 54.62%; The SiO2 grade is 1.00%; 4) Shaking table sorting comparison Another sample underwent a shaker sorting process, as detailed below: The ilmenite concentrate was refined and purified using a shaking table.

[0124] The concentrate 1 obtained by the shaking table treatment of the product with a thickness of -0.3 and +0.1 mm was combined with the concentrate 2 obtained by the shaking table treatment of the product with a thickness of -0.1 mm. Water was added to adjust the feed concentration to 25%, and the concentrate was fed evenly to the inlet of the shaking table. The flow rate of the shaking table washing water was 0.12 L / s. The mixture was filtered with filter paper, dried at 100℃, weighed, and then the contents of titanium and silicon were tested.

[0125] The results of testing on ilmenite concentrate 2-1 are as follows: The TiO2 grade is 48.81%; The SiO2 grade is 7.41%; 5) Results Analysis The TiO2 grade processed by the method of the present invention is 54.62%, while the TiO2 grade processed by shaking table separation is 48.81%, representing an increase of 11.9% in TiO2 grade.

[0126] The comparison of the above data shows that the method of the present invention significantly improves the TiO2 grade compared to the existing shaking table sorting method.

[0127] 3. Comparison of quartz sand deposits 1) Use of standards and equipment Use the standards and testing equipment described in section 3, "Product Testing," above.

[0128] 2) Sample source The sample is the raw ore collected by this invention. After screening and grading, the product with particle size of -0.71+0.1mm and -0.71+0.3mm was obtained. The middle ore 4 and middle ore 5 were obtained after being treated by the shaking table by the method of this invention. The above products were mixed evenly and divided into two portions, each 10kg.

[0129] 3) Using the method of the present invention The +0.3mm particle size product is purified by magnetic separation using the method described in Example 2 of this invention to refine quartz sand concentrate 2-1.

[0130] The +0.71mm product was crushed to -0.71mm using a sand crusher. The -0.1mm particle size product was then screened out using a 0.1mm standard sieve. The product on the sieve was combined with the -0.71mm and +0.3mm particle size products to form quartz sand feed. Water was added to adjust the feed concentration to 25%, and the mixture was poured into the feed hopper of a SLon-100 periodic pulse high gradient magnetic separator. The magnetic field strength was set to 13000 Oe for magnetic separation. The mixture was then filtered through filter paper, dried at 100℃, weighed, and the silicon content was determined.

[0131] The test results show that the SiO2 grade of quartz sand concentrate 2-1 is 98.23%.

[0132] 4) Comparison of selected shaking beds The +0.3mm particle size product is made by selecting and purifying concentrate using a shaking table 2-2.

[0133] The +0.71mm product was crushed to -0.71mm using a sand crusher. The -0.1mm particle size product was then screened out using a 0.1mm standard sieve. The product on the sieve was combined with the -0.71mm and +0.3mm particle size products to form quartz sand feed. Water was added to adjust the feed concentration to 25%, and the ore was fed evenly to the inlet of the shaking table. The flow rate of the shaking table washing water was 0.04L / s. The ore was then filtered through filter paper, dried at 100℃, weighed, and the silicon content was determined.

[0134] The test results show that the SiO2 grade of quartz sand concentrate 2-2 is 98.00%.

[0135] 5) Results Analysis The SiO2 grade of the quartz sand concentrate 2-1 obtained by the method of the present invention is 98.23%, and the SiO2 grade of the quartz sand concentrate 2-2 obtained by shaking table beneficiation is 98.00%, with an increase of 0.23% in SiO2 grade.

[0136] The comparison of the above data shows that the method of the present invention significantly improves the SiO2 grade compared to the existing shaking table cleaning method. This is because the main impurities in SiO2 at this grade are titanium and iron, and it is extremely difficult to improve the grade due to the limitations of physical impurity removal methods.

[0137] Experiment 3 1. Sampling Instructions 1) Sampling Arrangement The sampling point is located in another coastal fine-grained zirconium-hafnium sedimentary sand deposit section in Hepu County, Beihai City.

[0138] The sampling points are mainly distributed in the secondary marine terraces, with lithology mainly consisting of medium to coarse clay sand. The samples come from all the basic analysis samples, heavy sand samples, grain size distribution samples, and the remaining core samples, totaling 41 boreholes. The boreholes are evenly distributed throughout the entire survey area, and the cores are covered from the surface to the depth, are representative, and meet the requirements for mineral processing samples.

[0139] 2) Sampling method The sampling method used was 1 / 2 or 1 / 4 core splitting, with a core diameter of 110 mm.

[0140] 3) Sample preparation instructions The samples were packed in about 30 white woven bags. Since the test was conducted using all the drilled sub-samples, there was no need to mix the samples at this time. All the samples were simply mixed evenly into one sample.

[0141] 2. Ore Description 1) Ore structure Gravelly structure, coarse-medium-fine sand structure, silty sand structure.

[0142] 2) Ore sample structure The ore has a loose, layered structure.

[0143] 3) Mineral grain size In the raw ore samples, they are more concentrated in the -0.3mm particle size samples. In the zircon concentrate of the beneficiation process test, the major diameter of zircon is mostly between 0.015-0.3mm, with some slightly larger ones, the largest reaching 0.35mm. The minor diameter is mainly between 0.01-0.12mm, with some reaching 0.15mm. Among them, the particle size of colorless transparent zircon and pink zircon is generally larger than that of rose zircon.

[0144] 4) Main mineral characteristics Zircon is one of the main useful minerals in the sample. Single-mineral qualitative and quantitative analysis of zircon using electron probe microanalysis showed that it is mainly composed of ZrO2, TiO2 and SiO2, with small amounts of Hf, Al, K, Mg and other elements.

[0145] The zircon in the ore sample is mostly in the form of subhedral columnar, broken columnar, sub-cylindrical granular, and granular, with a small amount in columnar granular and rounded granular. The roundness is low and the transport traces are not obvious, suggesting that it is close to the parent rock. The degree of liberation of the individual minerals is over 90%, which is relatively high. The mineral structure is relatively stable and there are no other minerals embedded in it, making it relatively easy to enrich in subsequent beneficiation tests.

[0146] 5) Multiple chemical analyses of the raw ore Table 10 Results of Multi-Element Analysis of Raw Ore

[0147] 6) Raw ore screening analysis Table 11 Results of raw ore screening analysis

[0148] 3. Mineral Processing Results 1) Standards and Equipment The testing equipment and methods shall be carried out in accordance with the aforementioned "3. Product Testing".

[0149] 3) Mineral processing methods The samples were processed using the method described in Example 2 of this invention, and the results of the tests are as follows: The TiO2 grade of the raw ore is 0.61%; The SiO2 grade of the raw ore is 87.63%.

[0150] The ZrO2 grade of the raw ore is 354 ppm (0.0354%).

[0151] The ZrO2 grade of crude concentrate 1 (0.3-0.1 mm particle size) is 5847 ppm, and the ZrO2 grade of crude concentrate 2 (0.1 mm particle size) is 4737 ppm.

[0152] The TiO2 grade of concentrate 1, with a particle size of -0.3 to +0.1 mm, is 45.02%, and the ZrO2 grade is 50603 ppm.

[0153] The TiO2 grade of the -0.1mm particle size product concentrate 2 is 38.59%, and the ZrO2 grade is 94232ppm.

[0154] The zirconium crude concentrate has a ZrO2 grade of 233,878 ppm and a TiO2 grade of 17.05%. The TiO2 grade of the ilmenite concentrate is 52.38%.

[0155] The ZrO2 grade of the zircon concentrate is 558,205 ppm (55.82%). The SiO2 grade of the quartz sand concentrate is 98.36%.

[0156] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, the phrase "comprising an element defined as..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0157] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore, characterized in that, include: The raw ore was crushed, prepared into a solution, stirred and dispersed, and then screened and classified to obtain the following particle size products: +0.71mm, -0.71+0.3mm, -0.3+0.1mm and -0.1mm; The product with a particle size of -0.3 to +0.1 mm is separated by a shaking table to obtain coarse concentrate 1 and coarse tailings 1. The coarse concentrate 1 is then further separated by a shaking table to obtain concentrate 1 and middlings 4. The -0.1mm particle size product is separated by a shaking table to obtain rough concentrate 2 and rough tailings 2. The rough concentrate 2 is then further separated by a shaking table to obtain concentrate 2 and middlings 2. The magnetically separated concentrate obtained by wet magnetic separation of concentrate 1 and / or concentrate 2 is ilmenite sand concentrate.

2. The method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore according to claim 1, characterized in that, The parameters for shaking table sorting, shaking table fine selection, and shaking table sweeping of particles in the -0.3 to +0.1 mm particle size range are as follows: The stroke range of the shaking table is 9-17mm, the stroke rate range is 280-460 strokes / min, and the slope of the table surface ranges from 0-10°.

3. The method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore according to claim 2, characterized in that, For shaking table separation, shaking table cleaning, and shaking table scavenging of particles ranging from -0.3 to +0.1 mm, the feed concentration is 10-20%, and the flushing water flow rate is 0.05-0.14 L / s.

4. The method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore according to claim 1, characterized in that, The parameters for shaking table sorting, shaking table fine selection, and shaking table sweeping of particles in the -0.1mm size range are as follows: The stroke range of the shaking table is 2-10mm, the stroke rate range is 475-930 strokes / min, and the slope of the table surface ranges from 1-2°.

5. The method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore according to claim 4, characterized in that, For shaking table separation, shaking table cleaning, and shaking table scavenging of particles in the -0.1mm size, the feed concentration is 15-25%, and the flushing water flow rate is 0.05-0.12L / s.

6. The method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore according to claim 3 or 5, characterized in that, The coarse tailings 1 are scavenged by a shaking table to obtain middlings 1 and middlings 5. Middlings 1 is then separated by the shaking table. The coarse tailings 2 are scavenged by a shaking table to obtain middlings 3 and discharged tailings; The medium ore 2 and / or medium ore 3 are separated by shaking tables.

7. The method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore according to any one of claims 1-6, characterized in that, The wet magnetic separation process uses a 1.5mm gap sorting box with a magnetic field strength range of +7000-20000 Oe and a pulp concentration range of 15-30%.

8. The method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore according to claim 1, characterized in that, The beneficiation of quartz sand concentrate includes: The +0.71mm particle size product was crushed and screened to obtain the following particle size products: +0.71mm, -0.71mm, and -0.1mm. The -0.71+0.1mm and -0.71+0.3mm particle size products are combined with the aforementioned middle ore 4 and middle ore 5, and after magnetic separation, magnetic minerals are removed to obtain quartz sand concentrate. The magnetic field strength for magnetic separation is 0.7-1.6T; -0.1mm particle size products are treated as tailings for external discharge.

9. The method for beneficiating ilmenite from coastal sedimentary fine-grained zirconium-hafnium ore according to claim 8, characterized in that, The magnetic field strength is 1.3T.